Badania wykopaliskowe średniowiecznego cmentarzyska i osady w Miliczu: motywacje, cele, konteksty - Justyna Kolenda (Przegląd Archeologiczny, 2023)
The article  considers the factors determining the results of excavations and the relationship between the results obtained and the views expressed about the past by researchers/archaeologists. The author considers the extent to which and how the attitude of the researcher and the choice of method(s) of exploration of cultural stratification determine the amount of information obtained. These considerations are conducted on the basis of the theory of scientific cognition formulated in the interwar period by the Lviv microbiologist Ludwik Fleck. According to his assumptions, this was supposed to change the thinking of the time about, among other things, truth as a real existing entity or the objectivity of scientists' findings. Fleck's theory concerns science in the broadest sense of the term, the principles and rules governing its cognition, and in this form it was (and still is) applied by specialists in various disciplines. In this article, the theory of the Lviv microbiologist has been used to highlight the factors that determined the results of excavations carried out by two teams exploring the medieval burial ground and settlement of Milicz in 1953 and in 1960-1962.